Real-time analysis of multiple anion mixtures in aqueous media using a single receptor - Havel, Vaclav; Yawer, Mirza Arfan; Sindelar, Vladimir (Chemical communications (Cambridge, England), 2015)
Bambusuril-based receptors have been used in conjunction with (1)H NMR spectroscopy to recognize mixtures of inorganic anions in aqueous solutions. This was achieved by examining complexation-induced changes in the receptors' (1)H NMR fingerprints. This approach enables the simultaneous identification of up to 9 anions and the quantification of up to 5 anions using a single receptor in DMSO-d6 containing 5% D2O. Toxic perchlorate was recognized and quantified at 0.1 μM (1.8 ppb, mol mol(-1)) concentration in pure water.
Keywords: roztoky; Water; Imidazoles; Anions; Protons; protony; Time Factors; Molecular Conformation; voda; anionty; magnetická rezonanční spektroskopie; Solutions; molekulární konformace; imidazoly; Magnetic Resonance Spectroscopy; Macrocyclic Compounds; makrocyklické sloučeniny; časové faktory